2008
DOI: 10.1021/ja077772g
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated Bis(phenoxyketimine)titanium Complexes for the Living, Isoselective Polymerization of Propylene:  Multiblock Isotactic Polypropylene Copolymers via Sequential Monomer Addition

Abstract: A series of bis(phenoxyketimine)titanium dichloride complexes were synthesized and evaluated as catalysts for living, isoselective propylene polymerization upon activation with methylaluminoxane (MAO). Catalysts bearing phenoxyketimine ligands with different substituents at the ortho and para positions of the phenolate ring and substituents at the ketimine carbon were investigated. The identity of the ketimine substituent had the largest effect on the activity and isoselectivity of propylene polymerization. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
94
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(94 citation statements)
references
References 45 publications
0
94
0
Order By: Relevance
“…The results indicated that the coupling reaction could be catalyzed by either Pd(0) or Pd(II) catalyst, and Pd(PPh 3 ) 4 provided the highest yield of target product 3 (87% entry 4). Subsequently, a series of bases were investigated, the results suggested that bases have dramatic effects on the yields of cross-coupling product (entries [4][5][6][7][8]. We were delighted to observe the reaction provided target product 3 in 97% yield in the presence of 3 equiv.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The results indicated that the coupling reaction could be catalyzed by either Pd(0) or Pd(II) catalyst, and Pd(PPh 3 ) 4 provided the highest yield of target product 3 (87% entry 4). Subsequently, a series of bases were investigated, the results suggested that bases have dramatic effects on the yields of cross-coupling product (entries [4][5][6][7][8]. We were delighted to observe the reaction provided target product 3 in 97% yield in the presence of 3 equiv.…”
Section: Resultsmentioning
confidence: 99%
“…As listed in Table 2, a series of N-aryltrifluoroacetimidoyl chlorides and aryl boronic acids were investigated under the optimized conditions. Initially, a series of aryl boronic acids bearing different substitutes were tested by their reaction with substrate 1a or 1b (entries [1][2][3][4][5][6][7][8]. The results revealed that both electron-rich and electron-deficient phenyl boronic acids are suitable substrates for the coupling reaction and provided the corresponding trifluoromethyl arylketoimines in good to excellent yields (entries [1][2][3][4].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, another research group has revealed that Ti _ FI catalyst 32 bearing a phenyl group on the imine-C can induce isoselective living propylene polymerization and form moderately isotactic and nearly monodisperse PPs (0 polymerization; Mw/Mn 1.11, Mn 27,900, mmmm 53%, Tm 69.5 ), probably because of the suppression of the site-inversion process by the steric congestion provided by the phenyl group on the imine-C 108), 109) . The corresponding Ti _ FI catalysts bearing a sterically encumbered group at the R 2 position (which may produce higher tacticity PPs) exhibit virtually no reactivity toward propylene.…”
Section: Monodisperse Polymers (Living Polymers)mentioning
confidence: 99%